The role of the nearest relative in mental health law. (26th November 2020) - Griffith, Richard
Abstract : Richard Griffith, Senior Lecturer in Health Law at Swansea University, considers the role of the nearest relative, a statutory friend, appointed for patients detained under the Mental Health Act 1983